Laboratory and in situ sound absorption measurement under a synthetized diffuse acoustic field. Issue 4 (December 2019) - Robin, Olivier; Berry, Alain; Kafui Amédin, Celse; Atalla, Noureddine; Doutres, Olivier; Sgard, Franck
This article reports numerical and experimental results concerning the estimation of the diffuse field sound absorption coefficient of several different materials under a synthetized diffuse acoustic field excitation in laboratory and in situ conditions. The proposed measurement method is based on a sound field reproduction approach and a synthetic array of acoustic monopoles facing the material to be tested. Numerical simulations are first conducted to optimize the geometrical parameters of the method and to compute theoretical sound absorption coefficients of the considered materials. Measurements on a set of six typical acoustic materials are then conducted following the standardized reverberant room method as well as the proposed approach in a hemi-anechoic room and in two realistic rooms. Albeit showing limitations in the low-frequency domain, the proposed method enables a significant reduction of the tested specimen dimensions compared with the reverberant room method and allows performing tests in non-ideal acoustic environments.